2009
DOI: 10.1536/ihj.50.73
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan Decreases Plasma Levels of Asymmetrical Dimethyl-L-Arginine and Improves Lipid and Glucose Metabolism and Vascular Function

Abstract: SummaryTelmisartan is an angiotensin II receptor blocker (ARB) and also an activator of peroxisome proliferator-activated receptor-γ (PPAR-γ). We investigated whether telmisartan improves vascular endothelial function in patients with essential hypertension with the production of endothelial nitric oxide synthase (eNOS) through PPAR-γ.Telmisartan was administered to 15 patients with essential hypertension. To assess vascular function, asymmetric dimethylarginine (ADMA), an eNOS inhibitor synthesized by endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…24 Furthermore, the results regarding LDL cholesterol levels are somewhat surprising, because previous studies have shown that ARBs either have no effect or decrease LDL cholesterol. 15,28,[35][36][37][38] In fact, all of the studies using telmisartan did show a positive effect. The discrepancy between our results and the published data may relate to the doses used.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, the results regarding LDL cholesterol levels are somewhat surprising, because previous studies have shown that ARBs either have no effect or decrease LDL cholesterol. 15,28,[35][36][37][38] In fact, all of the studies using telmisartan did show a positive effect. The discrepancy between our results and the published data may relate to the doses used.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, it has been indicated that drugs that work on the renin-angiotensin system, such as ARB and angiotensin-converting enzyme, possess the ADMA reduction action, [16][17][18] and that telmisartan having the PPAR-g activation action particularly reduces ADMA. 19,20 Regarding the correlation between EPA and ADMA, Eid et al 21 conducted a study in which n-3 polyunsaturated fatty acid was given to patients with hyperlipidemia. They reported that although no change in ADMA was observed in the group, the decrease in the L-arginine/ADMA ratio because of aging was more suppressed than it was in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that pharmacological blockade of reninangiotensin system (RAS) by angiotensin-II type 1 receptor blocker (ARB) class of antihypertensive agents such as telmisartan offers favorable cardiovascular effects [17][18][19]. Its partial peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist activity which is achievable at therapeutic doses is responsible for anti-inflammatory, antioxidative and antiproliferative effects on vascular wall, thus reducing the risk for atherosclerosis, in addition to improving glucose and lipid profiles [20].…”
Section: Introductionmentioning
confidence: 99%